Potensi dan Tingkat Kematangan In vitro Oosit Sapi Peranakan Simmental - Jaswandi Jaswandi; D. Mardona; F. Arlina; Z. Udin (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The present research was conducted to investigate the potency and viabitity of oocytes of Simmental cattle for production of embryo in in-vitro method. Oacytes were collected from the ovaries of slaughtered Simmental cattle. At first, the ovaries were cleaned and measured for weigh, length, diameter and thickness. The ovaries were then sliced to collect oocyte follicles. The collected oocytes which were devided into 3 groups based on length size (<2, 2-6 and >6 mm) were kept in ringer solution (0,9 % Nacl) by temperature of 35oC. By using microscope the physical performances of the oocytes were observed and then classified into 3 different qualities of A, B and C/D. The oocytes of A ond B quality were kept in TCM-199 medium for maturity process. Their viability was described as percentage af oocytes which reach metaphase II (M-II). stage during the proces of maturity. The data was statistically analyzed by t-test. Results of the experiment showed that the physical measurement af ovaries were found significant diferent (P>0,05) between the left and right sides, but the potency of follicles from the both sides were not significant different (P>0,05). The percentage of oocytes reach the metaphase II stage was about 51,28 s/d 13,65 %. It was concluded that Simmental has a high the potency and viability oocytes for embryos production in vitro.